Chemoselective Oxime Reactions in Proteins and Peptides by Using an Optimized Oxime Strategy: The Demise of Levulinic Acid. Issue 18 (22nd October 2013) - Agten, Stijn M.; Suylen, Dennis; Ippel, Hans; Kokozidou, Maria; Tans, Guido; van de Vijver, Pieter; Koenen, Rory R.; Hackeng, Tilman M.
<x xml:space="preserve">Abstract</x> Selecting the right partner faster: In protein chemoselective conjugation, the use of levulinic acid for ketone introduction leads to slow oxime formation and poor yield because of internal cyclization, especially at low concentrations. A mechanism for cyclization is proposed and alternative keto‐acids have been tested. These showed faster formation of oximes without side products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>